Education Empowerment of Madrasah at Fisherman Society in Suku Laut Kuala Tungkal Jambi - Jailani, M. Syahran; Harun, Makmur Haji (AT-TA'LIM, 2020)
This study is aimed at revealing how is the Empowerment Education of Madrasah atÂ  Fisherman village Suku Laut Kuala Tungkal Jambi Province. Islamic schools are generally born from the initiation of society as a form of concern for the condition of the people, especially children in understanding the special religion of Islam as a matter of doubt. This research is conducted by using qualitative approach, where the stage is based on the opinion of Spradley . Data collection methods and data validity refer to Denzin and Lincoln and Guba. Result search, Â Islamic schools gait has contributed greatly to this country not only in providing a religious understanding, but also in participating to educate the children of the nation through the educational process that has lasted tens or even hundreds of years. In its journey, the empowerment of Islamic schools experienced various dynamics, commitment of Islamic school leadership, public awareness and supporting efforts became the issue that made Islamic schools hard to develop as expected.